Noninvasive Techniques for Management of Erythema Multiforme - Fabiana Martins; Debora Pallos; Jodkandlys Candeia; Rodrigo Zerbinati; Paulo Henrique Braz-Silva; Luana Campos (Case Reports in Dentistry)
An 18-year-old man was referred for a diagnosis of extensive oral lesions. During the interview, he reported a medical history of ganglionic tuberculosis, type 2 herpes infection, and significant weight loss due to dysphagia. Intraoral exam revealed multiple painful and ulcerated lesions covered by pseudomembrane. Lesions were observed on the labial and buccal mucosa, tongue, and soft palate. The laboratory findings included serum positivity for the Epstein-Barr virus, and salivary tests showed positive values for herpes simplex virus (HSV-2) and human herpesvirus (HHV-7). The diagnostic hypothesis was based on clinical findings and viral infection detected in the saliva, which triggered an immunological disorder, that is, erythema multiforme (EM). The treatment consisted of antimicrobial photodynamic therapy (aPDT), with substantial improvement in pain and healing as seen in the following twenty-four hours. Complete resolution of the lesions was achieved five days after the first session. Once the diagnosis of virus-induced EM was confirmed, noninvasive techniques (e.g., salivary tests and aPDT) were very successful and can be indicated for managing these lesions.